Harry Potter and the sorcerer's stone - Rowling, J. K.; GrandPre, Mary (New York Scholastic Inc., 1997)
Rescued from the outrageous neglect of his aunt and uncle, a young boy with a great destiny proves his worth while attending Hogwarts School for Witchcraft and Wizardry.
The Boy Who Lived -- The Vanishing Glass -- The Letters from No One -- The Keeper of the Keys -- Diagon Alley -- The Journey from Platform Nine and Three-quarters -- The Sorting Hat -- The Potions Master -- The Midnight Duel -- Halloween -- Quidditch -- The Mirror of Erised -- Nicolas Flamel -- Norbert The Norwegian Ridgeback -- The Forbidden Forest -- Through the Trapdoor -- The Man with Two Faces -- .
"Year 1"--Spine.
Sequel: Harry Potter and the Chamber of Secrets.
Read by Jim Dale.
880L
Keywords: Potter, Harry (Fictitious character); Granger, Hermione (Fictitious character); Weasley, Ron (Fictitious character); Hogwarts School of Witchcraft and Wizardry (Imaginary organization); Wizards; Magic; Schools; Accelerated Reader; Fantasy fiction; Witches -- Fiction; Wizards -- Fiction; School stories; England; Fantasy fiction